From Competition to Cooperation: Public Administration Reforms for Sustainable Cities - Warner, Mildred E. (Revista del CLAD Reforma y Democracia, 2017)
The 21st century is the urban century. Cities lead the way in growth and innovation, but also in inequality. How can public administration meet the challenges of demographic change, climate change and fiscal sustainability? The last decades of the 20th century gave primary concern to efficiency and championed the tools of decentralization and privatization. Competition was assumed to be the source of efficiency. But competition has limits, and in the 21st century, cooperation is the new reform. Public administration is giving increased attention to coordination, equity, and democratic voice. This requires a rebalancing of the relationship between the State and the market, and between the State and local government. Public values must be reinserted in the market for public service delivery. Cooperation across the inter-governmental system is required because innovative, new technologies have the potential to disrupt and fragment the city region. The challenge for public administration is to promote cooperation so that government can be the connective tissue that holds society together to address the challenges of the 21st century.